The concept of inclusive education and its psychological and pedagogical implementation in Russia against the background of current reforms in education - V. Sokolskaya, Marina (2020)
Various conceptual approaches to understanding inclusive education have historically been formed in international and Russian law, in social and pedagogical experience and the ways of its implementation are multifaceted. Bringing legislation in conformity with international standards requires substantial reform in all areas of law, the formation of a new conceptual and categorical apparatus, classifications, a new approach to the implementation of interaction between agencies, social welfare, education, and medicine. A serious psychological and pedagogical assessment of each step of these reforms is required, taking account of the delayed results, achieving unity and understanding in society. The authors of this paper substantiate the importance and necessity of developing and implementing a program to create a model of inclusive education for children with disabilities. The authors conclude that the contemporary general education program should include the changes and conditions required for the successful implementation of inclusive education, namely, accepting the individuality of each student, the provision of the special needs of each child and appropriate systematic training of teachers, psychologists, medical and social workers